Tindak Pidana Pencurian Yang Dilakukan Oleh Anak Dibawah Umur Dalam Tiga Perspektif - Dhyah Nur Fitriana; Ghoniyah Zulindah Maulidya (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
Theft is one of the actions that can damage relations between communities. If left alone, there will often be damage to public relations caused. Fatal if the perpetrators of theft from among minors who are still not of legal age. Because children are the future of the country, they will be the successors of the nation. Therefore, children must be facilitated with quality education so that later the country can develop well. Perpetrators of underage theft have different legal processes. Therefore, it is very interesting to conduct research and find solutions to the problem of minors as perpetrators of criminal acts, especially theft. The purpose of this study is to determine the position and punishment of cases of minors as perpetrators of theft crimes in three perspectives, namely the perspective of positive law, Islamic law, and the perspective of penology. This research uses normative law, namely library research that examines various secondary data so that it requires legal material as the main data